Predicting the impact of biocorona formation kinetics on interspecies extrapolations of nanoparticle biodistribution modeling. (January 2015) - Sahneh, Faryad Darabi; Scoglio, Caterina M; Monteiro-Riviere, Nancy A; Riviere, Jim E
Aim: To assess the impact of biocorona kinetics on expected tissue distribution of nanoparticles (NPs) across species.Materials & methods: The potential fate of NPs in vivo is described through a simple and descriptive pharmacokinetic model using rate processes dependent upon basal metabolic rate coupled to dynamics of protein corona.Results: Mismatch of time scales between interspecies allometric scaling and the kinetics of corona formation is potentially a fundamental issue with interspecies extrapolations of NP biodistribution. The impact of corona evolution on NP biodistribution across two species is maximal when corona transition half-life is close to the geometric mean of NP half-lives of the two species.Conclusion: While engineered NPs can successfully reach target cells in rodent models, the results may be different in humans due to the fact that the longer circulation time allows for further biocorona evolution.